2017
DOI: 10.1097/coh.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer in persons with HIV

Abstract: Purpose of Review Lung cancer is emerging as a leading cause of death in HIV infected persons. This review will discuss the latest scientific evidence regarding the mechanisms driving lung cancer risk in HIV infection, the clinical presentation of lung cancer in HIV infected persons, and recent data regarding the outcomes, treatment and prevention of lung cancer in this group. Recent Findings Increased risk of lung cancer in HIV infected persons is primarily due to higher smoking rates, but emerging evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 73 publications
1
67
0
2
Order By: Relevance
“…It was reported that highly active antiretroviral therapy improved the survival of patients with HIV, which increased the incidence of malignancies . Li et al .…”
Section: Safety Of Icis In Patients With Immune System Impairmentmentioning
confidence: 99%
“…It was reported that highly active antiretroviral therapy improved the survival of patients with HIV, which increased the incidence of malignancies . Li et al .…”
Section: Safety Of Icis In Patients With Immune System Impairmentmentioning
confidence: 99%
“…The risk of lung cancer is higher in HIV‐infected subjects than in the general population, and the higher smoking rate in the HIV‐infected population is one of the factors explaining this trend . In addition, recent studies show that immunosuppression by HIV and chronic inflammation are involved in oncogenesis . It is known that HIV infection is a risk factor for cancers of the conjunctiva and the lip .…”
Section: Enhancement Of Cancer Development By Coinfection With Multipmentioning
confidence: 99%
“…Key among these is tobacco cessation, as people with HIV continue to report higher rates of smoking than the general population. Sigel et al describe the importance of this in the observed elevated risk of lung cancer among people with HIV [8]. They further outline recent data supporting a possible role for CT screening for lung cancer in selected, high risk patients with HIV [9].…”
Section: Introductionmentioning
confidence: 99%
“…Work continues to establish specific approaches for people with HIV with common solid tumors including lung, anogenital, and hepatocellular malignancies [6–8]. As new therapeutic modalities are rapidly emerging for the general population in these and many other solid tumours, ongoing developmental therapeutic studies hold the promise of establishing clear safety and tolerability data to guide clinical care in people with HIV.…”
Section: Introductionmentioning
confidence: 99%